Evaluation of performance of small ruminants in smallholder Climate-Smart Villages of Lower Nyando, Kenya - Sila, Winfred (2020)
The productivity of small ruminants in developing countries remains low although the animals play an integral role in the livelihoods of smallholder farmers. Current information on their productive performance and contribution to the household incomes of smallholder farmers in Eastern Africa is limited. This study was implemented as part of an on-going small ruminant improvement project by the Climate Change Agriculture and Food Security (CCAFS) and the International Livestock Research Institute (ILRI) in Kericho and Kisumu Counties of the Lake Victoria basin of Kenya. The objective of this study was to evaluate productive performance and contribution to the household incomes of introduced improved small ruminants to the smallholder Climate Smart Villages of Lower Nyando. The information will contribute to knowledge on the productivity and costs of producing small ruminants and their roles in enhancing livelihoods of smallholder farmers grouped into “Climate Smart Villages”(CSV).